Strategi Adaptasi Petani Transmigran Di Kecamatan Wasile, Kabupaten Halmahera Timur, Provinsi Maluku Utara - Basuki, Natal; Suhardi, Suhardi; Mahmud, Haris (-, 2025)
The objectives of this study are: (1) to describe the reasons why transmigrant farming communities persist in Wasile Subdistrict; (2) to reveal the mindset and knowledge regarding the adaptation strategies of transmigrant farmers in Wasile Subdistrict. This study employs a constructivist paradigm and a qualitative approach. Data collection methods include observation, in-depth interviews, focus group discussions (FGD), and document studies. The conclusion is that the reason for survival is because Javanese transmigrant farmers possess an optimistic attitude towards the future of transmigration in Subaim Valley. The adaptation strategy used by Javanese transmigrant farmers in agriculture involves applying traditional farming by using the pranata mangsa (traditional Javanese seasonal calendar) as a reference in determining planting time